2017
DOI: 10.5897/jahr2017.0432
|View full text |Cite
|
Sign up to set email alerts
|

Water handling and low cost treatment practice of peoples living with human immunodeficiency virus (HIV) in Arba Minch Town, Southern Ethiopia, 2016

Abstract: Women of reproductive age account for nearly half of all HIV-infected people worldwide. Childbearing intention among HIV-infected women is complicated by social and reproductive concerns related to their HIV status. We conducted a cross-sectional study of HIV-infected and HIV-uninfected sexually active South African women aged 17 to 21 in order to compare their childbearing intentions and to identify predictors of the desire to have children among women with HIV. We found the rate of childbearing intention to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…The similarity of the populations and study designs might have created the correspondence in results. Nonetheless, fertility desire among HIV-positive women reported in different parts of the country and in Africa, for example, Addis Ababa (54.6%), Harari (52.9%), Tigray (45.5%), Oromia (47.5%), and South Africa (80%), was higher than our finding 2529. This might be due to the following circumstances: the study in Addis Ababa included both male and female HIV positive clients, the literature indicated that fertility desire among men was higher than among women and that might have increased the prevalence of the desire in the study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The similarity of the populations and study designs might have created the correspondence in results. Nonetheless, fertility desire among HIV-positive women reported in different parts of the country and in Africa, for example, Addis Ababa (54.6%), Harari (52.9%), Tigray (45.5%), Oromia (47.5%), and South Africa (80%), was higher than our finding 2529. This might be due to the following circumstances: the study in Addis Ababa included both male and female HIV positive clients, the literature indicated that fertility desire among men was higher than among women and that might have increased the prevalence of the desire in the study.…”
Section: Discussioncontrasting
confidence: 82%
“…This outcome is supported by other studies done in some areas in Ethiopia, African countries, Brazil and a Meta-analysis on fertility desire. This might be because participants who had regardless of the number might have attained the desired family sizes, and did not have future fertility desire 20,21,23,24,26,27,29,32,35,36,38. Women with regular partners had 3.52 times higher odds of future fertility desires.…”
Section: Discussionmentioning
confidence: 99%
“…Women are held more accountable for the survival of their marriages and are thus under more pressure to preserve the status quo (Baloyi, 2017;Chakare, 2013). In South Africa, the desire to become pregnant is high amongst both HIV-infected and HIV-uninfected women aged between 17 and 21 of whom the majority (67%) have not yet had children (Adler, Abar, Bennie, Sadeghi, & Bekker, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy decision-making for HIV-positive women is complicated because women have to think about family planning, unpredictable symptoms and prognoses of the disease, the transmission of HIV to sexual partners, the risk of their children becoming orphans, unreasonable community expectations, and their problematic life context amidst poverty, substance abuse and stigma that may compromise their parenting abilities (Adler et al, 2017;Ivanova, Hart, Wagner, Aljassem, & Loufty, 2012). An increased incidence of maternal deaths has been documented in South Africa, with almost a third of deaths in 2015 estimated to be AIDS-related (Mnyani, Buchmann, Chersich, Frank, & McIntyre, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation